Voluntary Out-of-Body Experience: An fMRI Study - Smith, Andra M.; Messier, Claude (Frontiers in Human Neuroscience, 2014)
The present experiment examined functional brain imaging patterns in a participant that reported being able, at will, to produce somatosensory sensations that are experienced as her body moving outside the boundaries of her physical body all the while remaining aware of her unmoving physical body. We found that the brain functional changes associated with the reported extra-corporeal experience were different than those observed in motor imagery. Activations were mainly left-sided and involved the left supplementary motor area, supramarginal and posterior superior temporal gyri, the last two overlapping with the temporo-parietal junction that has been associated with out-of-body experiences. The cerebellum also showed activation that is consistent with the participant’s report of the impression of movement during the extra-corporeal experience. There was also left middle and superior orbital frontal gyri activity, regions often associated with action monitoring. The results suggest that the extra-corporeal experience reported here represents an unusual type of kinaesthetic imagery.